2011
DOI: 10.1177/0194599811430809
|View full text |Cite
|
Sign up to set email alerts
|

Association between Otitis Media and Gastroesophageal Reflux

Abstract: The prevalence of gastroesophageal reflux disease in children with chronic otitis media with effusion/recurrent acute otitis media may be higher than the overall prevalence for children. Presence of pepsin/pepsinogen in the middle ear could be related to physiologic reflux. A cause-effect relationship between pepsin/pepsinogen in the middle ear and otitis media is unclear. Antireflux therapy for otitis media cannot be endorsed based on existing research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 23 publications
0
72
1
4
Order By: Relevance
“…The coexistence of gastro-esophageal reflux disease (GERD) and various respiratory disorders such as chronic rhinosinusitis or ear infection are reported by several past studies, although a causal link between them has so far not been sufficiently documented [35][36][37][38]. There are few studies showing the association between birth weight and stomach acidity/reflux.…”
Section: Health Conditionsmentioning
confidence: 99%
“…The coexistence of gastro-esophageal reflux disease (GERD) and various respiratory disorders such as chronic rhinosinusitis or ear infection are reported by several past studies, although a causal link between them has so far not been sufficiently documented [35][36][37][38]. There are few studies showing the association between birth weight and stomach acidity/reflux.…”
Section: Health Conditionsmentioning
confidence: 99%
“…The checklist was a modified version of an established list of criteria commonly used in systematic reviews. 23,24 The criteria are presented in Supplemental Table 7. Each item that met the inclusion criteria was assigned 1 point.…”
Section: Risk Of Bias and Assessment Of Qualitymentioning
confidence: 99%
“…Children with bottle feeding is another well known risk factor [1,3,8,10]; it is believed that passive immunity through the breast milk gives some protection [1], bottle-fed infants have higher nontypeable Haemophilus influenzae prevalence and lower immunoglobulin G antibodies [8]. Some studies found a role of Gastro esophageal reflux (GERD) disease [1,18]; GERD is found in 62.9% of patient with rOM. In fact pepsin/pepsinogen can be found in the middle ear in 85.3% of OM patients, a finding that can be explained by the reflux; however a cause and effect relationship cannot be established [18].…”
Section: Pathogenesismentioning
confidence: 99%